Reservoir sedimentation and its effect on storage capacity – A case study of Murera reservoir, Kenya. Issue 1 (1st January 2021) - Iradukunda, Parfait; Bwambale, Erion
Abstract: Lakes and dams located in sediment-laden rivers infill with time which reduces the storage capacity and consequently the quality of aquatic life. Anthropogenic activities in Kenya's Murera watershed have had significant impacts on storage capacity and water quality of Murera reservoir which inturn affects aquatic ecosystems. This study focused on the reservoir sedimentation assessment and examination of the sediment impacts on the storage loss in Murera reservoir dam. This was achieved by establishing the engineering concepts using the Bathymetric Survey System (BSS) comprising of navigation twin boat system (Dual Jon-boats) with an in-built Global Positioning System (GPS) for collecting spatial data. A multi-frequency acoustic system with frequencies of 200, 50 and 12 kHz was used to determine the reservoir bed level, part of sediment layers, and deposited sediments, respectively, to pre-impoundment levels of the reservoir. Data processing and analysis were performed using Depthpic 5.0.2 Surfer 15.5, and ArcGIS 10.3 software. The results show that the reservoir depth increased from the North part to the South part of the reservoir with a maximum depth of 7.78 m and the reservoir water storage of 707, 862.03 m 3 . Sediment deposition is concentrated in the southern part compared to the north part of the reservoir. The sediment layer thickness varied from 0 m up to 0.8 m (maximum) and the total sediment storage capacity of 117, 683.39 m 3, this implies that the reservoir lost 14% of its actual storage capacity. Results from this study provide pertinent information to policymakers in Kenya regarding the development, prioritization and assessment of mitigation and remediation strategies to address sedimentation problems in Kenya's water resources.